An Integrated Design of Electrodes for Flexible Dual‐Ion Batteries. Issue 4 (12th August 2022) - Li, Wen‐Hao; Li, Yue‐Ming; Yang, Jia‐Lin; Wu, Xing‐Long
Abstract: Due to the widespread employment of carbon materials in novel dual‐ion batteries (DIBs) with high energy density, they possess the potential for large‐scale energy storage and are inexpensive and environmentally friendly. However, drawbacks such as Al current collector corrosion and significant self‐weight, as well as lithium metal abuse and poor deposition reversibility, impair the energy density and cycle performance of lithium–graphite DIBs (Li−G DIBs), severely limiting their application potential. Therefore, an integrated electrode structure design was proposed. That is, the flexible graphite and single‐walled carbon nanotubes (SWCNTs) composite cathode (GSC), which is light‐weight and self‐supporting, and the self‐supporting lithium metal anode, which is loaded on the flexible carbon cloth (CC) derived from waste mask (Li@CC), were prepared. Not only were the impacts of current collector corrosion and active material exfoliation avoided on the electrochemical performance, but the areal loading of Li metal was also regulated and its reversibility of deposition enhanced. At a current density of 200 mA g −1, the constructed Li@CC//GSC full cell could release a specific capacity of 100.5 mAh g −1, and the capacity retention rate after 300 cycles was greater than 80 %. Moreover, the fabricated flexible Li@CC//GSC full cell is not only recyclable and produces less environmental pollution but also has potential applications in wearable devices. Abstract : Wear the change : Adopting an integrated electrode structure design improves the practicality of lithium–graphite dual‐ion batteries, and the prepared Li@carbon cloth//graphite and single‐walled carbon nanotubes composite full cell has the potential to be applied in the wearable field.